2003
DOI: 10.1103/physrevlett.90.082302
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of Back-To-Back High-pTHadron Correlations in CentralAu+AuCollisions atet al.

Abstract: Azimuthal correlations for large transverse momentum charged hadrons have been measured over a wide pseudorapidity range and full azimuth in Au+Au and p+p collisions at sqrt[s(NN)]=200 GeV. The small-angle correlations observed in p+p collisions and at all centralities of Au+Au collisions are characteristic of hard-scattering processes previously observed in high-energy collisions. A strong back-to-back correlation exists for p+p and peripheral Au+Au. In contrast, the back-to-back correlations are reduced cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 627 publications
(100 citation statements)
references
References 40 publications
3
95
0
1
Order By: Relevance
“…Comparing p + p and AA collisions, one might expect some changes in particle correlations: there could be an increase in correlations due to a possible increase of jet multiplicities in AA collisions or, conversely, some decrease due to the suppression of high p T back-to-back correlations [44]. Hoever, AA collisions exhibit long η range correlations (the "ridge") [45,46], which are not seen in p + p collisions and the origin of which is under investigation [47].…”
Section: E Nonflow Contribution For Various Methodsmentioning
confidence: 99%
“…Comparing p + p and AA collisions, one might expect some changes in particle correlations: there could be an increase in correlations due to a possible increase of jet multiplicities in AA collisions or, conversely, some decrease due to the suppression of high p T back-to-back correlations [44]. Hoever, AA collisions exhibit long η range correlations (the "ridge") [45,46], which are not seen in p + p collisions and the origin of which is under investigation [47].…”
Section: E Nonflow Contribution For Various Methodsmentioning
confidence: 99%
“…A significant suppression of high-p T hadron production relative to a simple binary collision scaling from p + p has been observed at RHIC in central Au + Au collisions [1]. Furthermore, it was found that jetlike correlations opposite to trigger jets are suppressed and that the azimuthal anisotropy in hadron emission persists out to very high p T [2][3][4]. In contrast, no suppression effects were seen in d + Au collisions [5][6][7][8], which has led to the conclusion that the observations made in Au + Au are attributable to the high-density medium produced in such collisions and not to initial-state effects.…”
Section: Introductionmentioning
confidence: 91%
“…It is the ratio between the measured particle spectra from Au + Au collisions normalized by the corresponding number of binary collisions and the measured spectra in elementary p + p collisions [36]. Together with the measurement of the disappearance of back-to-back high-p T hadron correlations in central Au + Au collisions attributed to interaction of the energetic jet particles with the formed medium [37], it was concluded that matter created at RHIC is highly interacting. The identified particle R AA from Au + Au collisions at 200 GeV shows that even the strange particle spectra are also suppressed, and there is a grouping of baryons and mesons with respect to their suppression in the intermediate-p T region.…”
Section: Nuclear Modification Factorsmentioning
confidence: 98%